Human histology : a text and atlas for physicians and scientists - Dudas, Bertalan (Academic Press, 2023)
Visually engaging and easy to use, Human Histology: A Text and Atlas for Physicians and Scientists covers the normal histology of every organ in the human body. This book presents full-page high-definition photomicrographs for organs and tissues, followed by a compact and simple-to-read description of the structures identified on the micrographs, offering a clear, visual understanding of this complex subject. With over 300 outstanding images, this reference is an invaluable resource for every clinical researcher and pathologist in need of easily accessible, relatively simple but detailed enough information on normal histology of different organs systems. Due to its compact, but detailed layout, the volume is an excellent tool for medical board review and can be recommended for medical students and histology course directors.